Extracellular RNAs: development as biomarkers of human disease. Issue 1 (28th August 2015) - Quinn, Joseph F.; Patel, Tushar; Wong, David; Das, Saumya; Freedman, Jane E.; Laurent, Louise C.; Carter, Bob S.; Hochberg, Fred; Keuren‐Jensen, Kendall Van; Huentelman, Matt; Spetzler, Robert; S. Kalani, M. Yashar; et al.
Abstract : Ten ongoing studies designed to test the possibility that extracellular RNAs may serve as biomarkers in human disease are described. These studies, funded by the NIH Common Fund Extracellular RNA Communication Program, examine diverse extracellular body fluids, including plasma, serum, urine and cerebrospinal fluid. The disorders studied include hepatic and gastric cancer, cardiovascular disease, chronic kidney disease, neurodegenerative disease, brain tumours, intracranial haemorrhage, multiple sclerosis and placental disorders. Progress to date and the plans for future studies are outlined.